Performance identification of the asynchronous electric drives by the spectrum of rotor currents - Vladimir L. Kodkin; Aleksandr Sergeevich Anikin; Aleksandr A. Baldenkov (Institute of Advanced Engineering and Science, 2019)
The efficiency of analyzing the rotor currents of asynchronous electric drives with frequency control is substantiated in the article. To assess the quality of torque generation in the engine it is suggested to use the spectral analysis of these currents and the fundamental harmonic, as the most accurate